Rethinking developmental toxicity testing: Evolution or revolution?. Issue 10 (12th February 2018) - Scialli, Anthony R.; Daston, George; Chen, Connie; Coder, Prägati S.; Euling, Susan Y.; Foreman, Jennifer; Hoberman, Alan M.; Hui, Julia; Knudsen, Thomas; Makris, Susan L.; Morford, LaRonda; Piersma, Aldert H.; et al.
Abstract : Background: Current developmental toxicity testing adheres largely to protocols suggested in 1966 involving the administration of test compound to pregnant laboratory animals. After more than 50 years of embryo‐fetal development testing, are we ready to consider a different approach to human developmental toxicity testing? Methods: A workshop was held under the auspices of the Developmental and Reproductive Toxicology Technical Committee of the ILSI Health and Environmental Sciences Institute to consider how we might design developmental toxicity testing if we started over with 21st century knowledge and techniques (revolution). We first consider what changes to the current protocols might be recommended to make them more predictive for human risk (evolution). Results: The evolutionary approach includes modifications of existing protocols and can include humanized models, disease models, more accurate assessment and testing of metabolites, and informed approaches to dose selection. The revolution could start with hypothesis‐driven testing where we take what we know about a compound or close analog and answer specific questions using targeted experimental techniques rather than a one‐protocol‐fits‐all approach. Central to the idea of hypothesis‐driven testing is the concept that testing can be done at the level of mode of action. It might be feasible to identify a small number of key events at a molecular or cellular level that predict an adverse outcome and for which testing could be performed in vitro or in silico or, rarely, using limited in vivo models. Techniques for evaluating these key events exist today or are in development. Discussion: Opportunities exist for refining and then replacing current developmental toxicity testing protocols using techniques that have already been developed or are within reach.